Information needs of clinical teams: analysis of questions received by the Clinical Informatics Consult Service - JEROME, Rebecca N; GIUSE, Nunzia B; WILDER GISH, Kimbra; SATHE, Nila A; DIETRICH, Mary S (Bulletin of the Medical Library Association, 2001)
To examine the types of questions received by Clinical Informatics Consult Service (CICS) librarians from clinicians on rounds and to analyze the number of clearly differentiated viewpoints provided in response. Questions were retrieved from an internal database, the CICS Knowledge Base, and analyzed for redundancy by subject analysis. The unique questions were classified into ten categories by subject. Treatment-related questions were analyzed for the number of viewpoints represented in the librarian's response. The CICS Knowledge Base contained 476 unique questions and 71 redundant questions. Among the unique queries, the top two categories accounted for 67%: treatment (36%) and disease description (31%). Within the treatment-related subset, 138 questions (59%) required representation of more than one viewpoint in the librarian's response. Questions generated by clinicians frequently require comprehensive, critical appraisal of the medical literature, a need that can be filled by librarians trained in such techniques. This study demonstrates that many questions require representation of more than one viewpoint to answer completely. Moreover, the redundancy rate underscores the need for resources like the CICS Knowledge Base. By critically analyzing the medical literature, CICS librarians are providing a time-saving and valuable service for clinicians and charting new territory for librarians.